GOOD INTENTIONS: AN EMPIRICAL COMPARISON BETWEEN THE PERFORMANCE OF GREEN AND CONVENTIONAL MUTUAL FUNDS - Blanchard, Camillo Thomas (2016)
Objectives and distinctive elements of the study: This dissertation investigates the performance of green mutual funds compared with their conventional counterparts. It represents a follow-up contribution to the still relatively small group of studies on the green mutual funds market. By enriching the empirical literature, this work could be a useful tool for investors willing to find answers on the real and measurable financial benefits of these more responsible and environmentally friendly investments. Another point of strength of this dissertation lies in the screening and subsequent sample matching process which gives the possibility to compare the funds in the most appropriate manner. Methodology: In the first part, an initial overview of the concepts related to socially responsible investments is presented. This section also provides the reader with some figures of this particular type of mutual funds’ market. Secondly, it follows an overview of the literature on green and SRI mutual funds. In the final section, an empirical analysis replicates some of the studies by comparing the performance between green and conventional mutual funds. In order to investigate the differences between the two categories, two lists of funds are retrieved from Bloomberg terminal according to their general attributes. An initial description of the samples together with an explanation of the funds’ screening process is reported. Subsequently, a final sample of 35 green funds domiciled in four EU countries referring to the period 2008-2016 is matched with other 35 conventional funds from the same domicile by using a statistical tool known as the Nearest-Neighbour matching estimator. Subsequently, a panel regression model is constructed to calculate the performance measure in the spirit of Jensen (1968) and to detect any difference between the two categories. In a final section a regression analysis also explores whether any difference was caused by external economic shocks (e.g. 2008 financial crisis) or enhanced by the political and legislative dynamics related to one of the four investigated countries in particular. Findings: The findings are in line with the previous literature. Both categories of funds are never able to over perform their market of reference. Particularly, results show that no statistically significant difference in performance is exhibited between the green and conventional portfolios. However, when studying the performance with a cross-country analysis, it is found that the UK domiciled green funds are significantly better performing than their conventional counterparts.